Current Practice vs. Guideline Based Imaging in Abdominal Radiology in the German Speaking Area: Results of an Online Survey - Schreyer, A. G.; Wessling, J.; Grenacher, L. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: The working group for abdominal imaging within the German Roentgen Society (DRG) performed an online survey amongst radiologist concerning the current status of techniques for abdominal imaging. The results of this survey were compared with the most recent guidelines.Materials and Methods: We performed an online survey open for all members of the DRG during a 76-day period with 65 questions and an overall estimated time for finishing the questionnaire of 15 minutes concerning technical specifications for abdominal radiological imaging. The results were evaluated using descriptive statistics.Results: 90 of all participants, who filled out the survey covering more than 80 % of the questions, were included in the statistical evaluation. 27 % of all participants were registered radiologists while 73 % represented radiologists working in a hospital. Most participants worked in a managerial position. The participants gave detailed information regarding the radiological techniques used in dedicated organ systems (esophagus, stomach, pancreas, liver, small intestines, colon) regarding acquired contrast phases and oral and intravenous administration of contrast medium.Conclusion: The results confirm that most radiologists participating in this survey perform their examinations and choose their modalities in conformity with the current existing clinical guidelines. Because most clinical guidelines do not specify radiological examinations in detail, there is a noteworthy heterogeneity of the acquired contrast phases and major divergence in terms of technical parameters. Therefore a joint radiological effort should be initiated for developing and publishing updated radiological parameters for abdominal imaging.Key Points:• In German speaking countries indications for abdominal radiological examinations are performed with a high compliance to published guidelines.• There is a significant heterogeneity regarding the acquisition of different contrast phases for parenchymal abdominal organs.• There is an urgent need to publish radiological recommendations and guidelines based on current radiological literature for radiological abdominal imaging.Citation Format:• Schreyer AG, Wessling J, Grenacher L. Versorgungsrealität vs. leitliniengerechte Bildgebung in der Abdominalradiologie im deutschsprachigen Raum: Ergebnisse einer Online-Umfrage. Fortschr Röntgenstr 2016; 188: 1 – 12
Keywords: abdomen; CT; diagnostic radiology; MR-imaging